Development & Screening Approach for Lipid Nanoparticle: A Review - Patel, Dilip; Kesharwani, Roohi; Gupta, Prof. Suresh (Asian Journal of Pharmaceutical Research and Development, 2015)
Since the beginning of the 1990s the lipid nanoparticles were getting a growing interest from the pharmaceutical technology research group’s world wide. Nowadays solid lipid nanoparticles (SLN), nanostructured lipid carriers (NLC) and lipid drug conjugate (LDC) have been already investigated as carrier systems for many applications. This review article explains what was the need to develop new concept for lipid Nanoparticle. SLN have a lot of problem like drug loading as well as drug expulsion on long time storage due to β modification of solid lipid, To overcome this NLC were developed. SLN & NLC are basically use for loading of hydrophobic drug where LDC developed to overcome such problem. The approach used to select the solid as well as liquid lipid were discus in this article which help in selecting appropriate lipid for formulation of lipid Nanoparticle.